Design and content validity of the Continuity of Care Across Levels of Care Questionnaire - Marín Sánchez, Alexandra; Gogeascoechea-Trejo, María del Carmen; Vélez Álvarez, Consuelo; Blázquez-Morales, María Sobeida Leticia; Pavón-León, Patricia; Nachón-García, María Gabriela; Cinta Loaiza, Dulce María (Revista Cuidarte, 2023)
Introduction: In the absence of continuity of care, actions aimed at the care of users with chronic non-communicable diseases (NCDs) may be omitted or duplicated, which can potentially worsen users’ health. In Mexico and Colombia, in particular, there is no instrument for assessing continuity of care that includes its three essential elements. Objective: To develop an instrument to assess care continuity across levels of care for users with NCDs in Mexico and Colombia and validate the content of the questionnaire through expert judgment of versions adapted to the Mexican and Colombian contexts. Materials and Methods: The Continuity of Care across Levels of Care Questionnaire was designed. The content validation process was carried out by experts using the Delphi technique. Sixteen experts were selected (8 per country). Questionnaire items were assessed in four categories: sufficiency, clarity, coherence, and relevance. Two assessment rounds were conducted to determine the level of experts’ agreement. Results: The questionnaire obtained an ‘Excellent’ overall Content Validity Coefficient in both countries (0.97). Discussion: This instrument, unlike others, assesses the continuity of care in a multidisciplinary manner across the three levels of care from the experience of users with NCDs. Conclusion: The questionnaire achieved the expected content validity using the Delphi technique to assess care continuity across levels of care for users with NCDs, according to the Mexican and Colombian contexts. How to cite this article: Marín Sánchez Alexandra, Gogeascoechea-Trejo María del Carmen, Vélez Álvarez Consuelo, Blázquez-Morales María Sobeida Leticia, Pavón-León Patricia, Nachón-García María Gabriela, Cinta Loaiza Dulce María. Diseño y validez de contenido del cuestionario continuidad del cuidado entre niveles asistenciales. Revista Cuidarte. 2023;14(2):e2773. http://dx.doi.org/10.15649/cuidarte.2773